New Insights on the Effects of Methylphenidate in Attention Deficit Hyperactivity Disorder - Pitzianti, Maria Bernarda; Spiridigliozzi, Simonetta; Bartolucci, Elisa; Esposito, Susanna; Pasini, Augusto (Frontiers in Psychiatry, 2020)
This narrative review provides an overview of the multiple effects of methylphenidate (MPH) in attention-deficit/hyperactivity disorder (ADHD) and its potential neurobiological targets. It addressed the following aspects: 1) MPH effects on attention and executive functions in ADHD; 2) the relation between MPH efficacy and dopamine transporter gene (DAT) polymorphism; and 3) the role of MPH as an epigenetic modulator in ADHD. Literature analysis showed that MPH, the most commonly used psychostimulant in the treatment of ADHD, acts on multiple components of the disorder. Marked improvements in attentional and executive dysfunction have been described in patients with ADHD during treatment with MPH, as well as reductions in neurological soft signs. MPH efficacy may be influenced by polymorphisms in the DAT, and better responses to treatment were associated with the 10/10 genotype. Innovative lines of research have suggested that ADHD etiopathogenesis and its neuropsychological phenotypes also depend on the expression levels of human endogenous retrovirus (HERVs). In particular, several studies have revealed that ADHD is associated with HERV-H over-expression and that MPH administration results in decreased expression levels of this retroviral family and a reduction in the core symptoms of the disorder. In conclusion, there is a confirmed role for MPH as an elective drug in the treatment of ADHD alone or in combination with behavioural therapy. Its effectiveness can vary based on DAT polymorphisms and can act as a modulator of HERV-H gene expression, pointing to targets for a precision medicine approach.